(untitled) (AYUSHDHARA, 2024)
Diabetes mellitus is a metabolic disorder mainly characterized by elevated blood sugar level or hyperglycemia. Type 2 Diabetes Mellitus (T2DM) is the most common form, accounting for about 90% of the total diabetic population and is a major cause of morbidity and mortality. The condition mainly occurs from insulin resistance and relative deficiency in insulin secretion. The condition hampers the patient’s quality of life with symptoms of polyuria, polyphagia, polydipsia, fatigue, weight loss, etc. Type 2 Diabetes Mellitus can be managed effectively in the initial phases with proper medication and lifestyle modification. The untimely treatment, chronicity of insulin resistance, and hyperglycemia can cause damage to multiple organs. In Ayurveda, the descriptions of Avaranajanya Madhumeha, which is a Medovahasrothodushti Vikara can be compared with T2DM as both seem analogous in etiopathogenesis and clinical features. The present study aims to evaluate the efficacy of Abhrakadi Yogam in managing Type II Diabetes Mellitus. The study was a consecutive case series done on an OPD basis. The study was conducted on ten subjects newly diagnosed with Type 2 Diabetes Mellitus, in whom Abhrakadi Yogam, 4gm thrice daily before food along with honey as Anupana was given for 90 days and 30 days follow up. Assessment was done on 0th, 91st and 121st day with subjective and objective parameters. All drugs possess Tridoshahara property which helps in controlling all the Doshas. The Deepana, Pachana, Lekhana, Vatanulomana and Rasayana properties of the trial drug helped in Amapachana, Kleda Shoshana, Medohara and Srothoshodhana, restoring Dhatu Sthirata thereby improving quality of life of patients. After treatment significant improvement was observed in assessment parameters. The study showed significant clinical efficacy and safety of the trial drug.